The Prevalence of Relative Afferent Pupillary Defects in Normal Subjects - Wilhelm, Helmut; Peters, Tobias; Lüdtke, Holger; Wilhelm, Barbara (Journal of neuro-ophthalmology, 2007)
BACKGROUND:Observational and pupillographic studies of small numbers of normal subjects have shown that a small (<0.3 log units) relative afferent pupil defect (RAPD) is present in a minority. We have extended the investigation of the prevalence of RAPD to a larger number of normal subjects. METHODS:A total of 102 subjects were examined by observation and pupillography. The swinging flashlight test was performed using neutral density filters for quantification. During the pupillographic procedure, light-emitting diodes were placed in front of each eye, alternately flashing for 2.5 seconds with a 0.5 second break. A binocular real-time pupillometer recorded the direct and consensual pupillary responses. After artefact detection and removal, the amplitudes of pupillary response were determined and plotted against stimulus intensity. The means of the direct and the consensual responses were used for automated calculation of RAPD. RESULTS:By observation, there was no RAPD in 87 (85%) subjects; there was an RAPD of 0.15 log units in 13 (13%), and an RAPD of 0.3 log units in 2 (2%). By pupillography, there was an RAPD of 0.07 log units in 53 (52%) subjects, an RAPD between 0.08 and 0.22 log units in 43 (42%) subjects, and an RAPD between 0.23 and 0.39 log units in 6 (6%) subjects. CONCLUSIONS:Observation and pupillographic measurements of the swinging light test in a large normal subject cohort has confirmed that an RAPD is present in a small minority but that it does not exceed 0.39 log units. The RAPD in these subjects may be explained by inaccuracy of measurement or by asymmetries in the connections between visual pathways and pretectal nuclei in the midbrain.